Perceived effectiveness of text vs. multimedia Location-Based Advertising messaging. (6th January 2009) - Xu, Heng; Oh, Lih-Bin; Teo, Hock-Hai
The emergence of mobile communication and positioning technologies has presented advertisers and marketers with a radically innovative advertising channel: Location-Based Advertising (LBA). Despite the growing attention given to LBA, little is understood about the differential effects of text and multimedia advertising formats on the mobile consumer perceptions and behaviours. This exploratory study empirically examines the effects of multimedia advertisements vis-a-vis text-based advertisements on consumer perceptions and behaviours in a simulated LBA environment. A structural model was formulated to test their effects on consumer perceptions of entertainment, informativeness and irritation. Results show that multimedia LBA messages lead to more favourable attitude, increase the intention to use the LBA application, and have significant impact on purchase intention. Furthermore, this study indicates the role of multimedia as a double-edged sword: on the one hand, it suggests that multimedia impose a higher level of irritation; on the other hand, it suggests that multimedia enhance the informativeness and entertainment value of LBA. Implications for theory and practice are discussed.